Establishment and application of a 10‐plex liquid bead array for the simultaneous rapid detection of animal species. (6th November 2019) - Mei, Mingzhu; Chen, Ru; Gao, Xiaobo; Cao, Yongchang; Weng, Wenchuan; Duan, Yanyu; Tan, Xin; Liu, Zhiling
Abstract: BACKGROUND: Meat fraud and adulteration incidents occur frequently in almost all regions of the globe, especially with the increase in the world's population. To ensure the authenticity of meat products, we developed a 10‐plex xMAP assay to simultaneously detect ten animal materials: bovine, caprine, poultry, swine, donkey, deer, horse, dog, fox and mink. RESULTS: This method was investigated by analyzing DNA extracts from raw muscle, muscle mixtures, meat products and animal feeds. Our results indicated that the species of interest can be identified, differentiated and detected down to 1 g kg −1 in binary mixtures or 0.01–0.001 ng of genomic DNA from specific species. Testing of 125 commercial samples showed a 97.4% coincidence rate with the method used in routine testing in our lab. CONCLUSION: These results indicated that the method established in this study could detect ten animal materials simultaneously within 3 h, which provides a new, useful tool for animal ingredient analysis in meat products and animal feeds. © 2019 Society of Chemical Industry